Reform with Unaccounted Uncertainty (Review of the Monograph: ‘The Reform of Rail Transport: Critical Analysis and the Problem of Estimating Efficiency’) - Anna Borisovna Bardal (Prostranstvennaâ Èkonomika, 2018)
The present work is a review of a monograph ‘The Reform of Rail Transport: critical analysis and the problem of estimating efficiency’ by Kibalov E.B. and Kin A.A., published by Institute of Economics and Industrial Engineering, Siberian Branch of RAS in 2017. The unquestionable merit of the monograph is an original author approach of complex application of decision theory methods, applied systems analysis, model apparatus of investment analysis, economic sociology, and economic publication, to one research task – studying the results of the rail transport reform in Russia. It is viewed by the authors as a large-scale institutional project with an investment component. The analysis of reform process and its results leads the authors to a conclusion about fundamental problem: not accounting for the uncertainty factor. The monograph formulates the authors’ concept of assessment of large-scale projects (institutional and investment) in uncertain situations and offers complex methods of their appraisal, including econometrical modeling and expert interviews. The main content is presented in five parts. The indisputable advantage of the monograph is the continuity with the previous works of the authors and the application of several decades’ worth of research results